2014
DOI: 10.1097/mbc.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and plasma levels of tissue factor and tissue factor pathway inhibitor in venous thromboembolism

Abstract: Tissue factor (TF) and tissue factor pathway inhibitor (TFPI) play important roles in coagulation. The aim of this study was to investigate the distributions of TF and TFPI polymorphisms in Koreans and to analyze the association of these genetic polymorphisms with plasma levels and development of venous thromboembolism (VTE). The polymorphisms TF 5466 A > G, TF -603 A > G, TFPI -287 T > C and TFPI -33 T > C were investigated in 40 Korean VTE patients and 40 age-matched and sex-matched controls by real-time PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…[27] There were 8 studies with 976 cases and 1780 controls for TFPI rs8176592 polymorphism. All were case-control studies, including 3 venous thromboembolism (VTE) studies, [27,28,34] 3 DVT studies, [29,35,36] 1 venous thrombosis study, [32] and 1 cerebral venous thrombosis (CVT) study. [33] Subjects were sampled from France, Australia, Denmark, Norway, India, Korean, and China.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27] There were 8 studies with 976 cases and 1780 controls for TFPI rs8176592 polymorphism. All were case-control studies, including 3 venous thromboembolism (VTE) studies, [27,28,34] 3 DVT studies, [29,35,36] 1 venous thrombosis study, [32] and 1 cerebral venous thrombosis (CVT) study. [33] Subjects were sampled from France, Australia, Denmark, Norway, India, Korean, and China.…”
Section: Resultsmentioning
confidence: 99%
“…There were 5 studies with 453 cases and 795 controls for TFPI rs10931292 polymorphism. All were case-control studies, including three VTE studies, [28,31,34] 1 DVT study, [30] and 1 venous thrombosis study. [32] Subjects were sampled from Australia, England, China, Norway, and Korea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating TF levels 40,41 and TF expression by blood cells 42,43 could be determined by genetic factors. We previously found that TF gene polymorphisms and haplotypes were associated with the risk of ischemic stroke at young age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study suggested that tissue factor and tissue factor pathway inhibitor played key roles in coagulation and acted as direct risk factors for VTE. [ 13 ] Although progresses have been achieved for the pathogenesis of VTE, the genetic mechanisms are far from being understood. Determination of the recurrence risk factors for VTE is still a vital health concern.…”
Section: Introductionmentioning
confidence: 99%